Influence of acute pancreatitis on the in vitro responsiveness of rat mesenteric and pulmonary arteries - Camargo, Enilton A.; Delbin, Maria Andreia [UNESP]; Ferreira, Tatiane; Landucci, Elen C. T.; Antunes, Edson; Zanesco, Angelina [UNESP] (Biomed Central Ltd., 2008)
Background: Acute pancreatitis is an inflammatory disease characterized by local tissue injury and systemic inflammatory response leading to massive nitric oxide (NO) production and haemodynamic disturbances. Therefore, the aim of this work was to evaluate the vascular reactivity of pulmonary and mesenteric artery rings from rats submitted to experimental pancreatitis.Male Wistar rats were divided into three groups: saline (SAL); tauracholate (TAU) and phospholipase A(2) (PLA(2)). Pancreatitis was induced by administration of TAU or PLA(2) from Naja mocambique mocambique into the common bile duct of rats, and after 4 h of duct injection the animals were sacrificed. Concentration-response curves to acetylcholine (ACh), sodium nitroprusside (SNP) and phenylephrine (PHE) in isolated mesenteric and pulmonary arteries were obtained. Potency (pEC(50)) and maximal responses (E(MAX)) were determined. Blood samples were collected for biochemical analysis.Results: In mesenteric rings, the potency for ACh was significantly decreased from animals treated with TAU (about 4.2-fold) or PLA(2) (about 6.9-fold) compared to saline group without changes in the maximal responses. Neither pEC(50) nor E(MAX) values for Ach were altered in pulmonary rings in any group. Similarly, the pEC(50) and the E(MAX) values for SNP were not changed in both preparations in any group. The potency for PHE was significantly decreased in rat mesenteric and pulmonary rings from TAU group compared to SAL group (about 2.2- and 2.69-fold, for mesenteric and pulmonary rings, respectively). No changes were seen in the E(MAX) for PHE. The nitrite/nitrate (NO(x)(-)) levels were markedly increased in animals submitted to acute pancreatitis as compared to SAL group, approximately 76 and 68% in TAU and PLA(2) protocol, respectively.Conclusion: Acute pancreatitis provoked deleterious effects in endothelium-dependent relaxing response for ACh in mesenteric rings that were strongly associated with high plasma NO(x)(-) levels as consequence of intense inflammatory responses. Furthermore, the subsensitivity of contractile response to PHE in both mesenteric and pulmonary rings might be due to the complications of this pathological condition in the early stage of pancreatitis.